Healthcare workers` motivation in preventive activities - Trifunović, Boban; Fišeković Kremić, Marina (General Practice, 2023)
Introduction. Successful implementation of all activities, especially in the area of preventive medicine, healthcare institutions may accomplish only if their employees are highly motivated and properly rewarded for their work. The best motivational system should be designed so the employees get the rewards that matter to them. That is why research into the motives and needs of employees appears as a necessary prerequisite for the effectiveness of motivation. Objective. We aimed at examining the most important motivational factors for preventive activities in healthcare workers. Method. The research was conducted, as a case study, in the Primary Healthcare Center (PHC), Golubac from December 2019 to December 2020. We analyzed the results of the preventive activities of healthcare workers from the PHC Golubac during project activities in 2020 and compared them to the results from 2018. Employees` attitudes towards motivational factors were analyzed based on the conducted individual interviews and surveys. Results. The results of preventive actions in 2020, through project activities, were significantly better than those in 2018. The diabetes screening response was 42%, the realization of blood pressure measuring in diabetic patients was 58%, and HbA1c was measured in 34% of diabetics in 2020. In 2018 screening realization was 15%, blood pressure was measured in 50% of diabetics, and HbA1C in 10%. The most important motivational factors for healthcare workers were the importance of preventive activities for the people`s health, the participation of the manager as the project leader, the equipment gained during the project that will improve their work, clearly defined goals, and personal responsibility for the project`s success. Conclusion. The motivation of healthcare workers is of great importance for the successful implementation of preventive activities. Our research provides information for healthcare managers on ways to improve their employees` motivation. Keywords: motivation,